The pharmaceutical development of a fixed combination anti-tuberculosis dosage form - Ebrahim, Salima (My University, 1998)
Despite the availability of highly effective treatment regimens for tuberculosis, cure rates remain low for tuberculosis mainly due to patient non-compliance which results in the occurrence of multi drug resistance tuberculosis. To avoid the problem of further creation and propagation of multi drug-resistant tuberculosis, patients should be given fixed-dose combinations of anti-tubercular drugs whenever self-administration of drugs iJ permitted. During this study, an anti-tuberculosis extemporaneous powder for suspension was optimized in order to formulate a fixed combination of rifampicin. isoniazid, pyrazinamide and ethambutol hydrochloride as a powder to be ' . constituted with water by the patient prior to administration. Once an effective manufacturing method was established, different suspending agents were evaluated by their influence on powder flow properties and sedimentation volume on the powder blends. Sodium starch glycollate was chosen as the suspending agent of choice because as the concentration of sodium starch glycollate was increased, the powder flow properties of the powder blends improved. The sedimentation volume also. increased with the increasing concentration of sodium starch glycollate in the powder blends. A suitable flavour and colour was also determined to increase the acceptability of the preparation to the patient. Liquorice flavour was the most acceptable in terms of colour and flavour. An evaluation of the dissolution characteristics of the extemporaneous powder for suspension was also conducted in comparison to the dissolution profiles from commercially available tablet dosage forms. The dissolution rates from the powder tor suspension for rifampicin, isoniazid and pyrazinamide was faster than from the commercially available tablet dosage form, while the dissolution race of ethambutol HCl from the powder closely resembles the dissolution profile from the Rolab-Ethambutol HCIR tablet dosage form Therefore. a fixed combination powder for suspension was achieved and with its ease of administration would increase the compliance amongst tuberculosis patients. and increase therapeutic outcomes.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand In partial fulfilment of the requirements for the degree of Master of Science in medicine (Pharmaceutical affairs) Johannesburg, 1998
Keywords: Antitubercular agents; Tuberculosis drug therapy